Simulation Study of Fluid Flow and Estimation of a Heterogeneous Porous Media Properties Using Lattice Gas Automata Method - Dedy Kristanto; Windyanesha Paradhita (Journal of Petroleum and Geothermal Technology, 2020)
Most models used in reservoir simulation studies are on the scale of meters to hundreds of meters. However, increasing resolution in geological measurements results in finer geological models. Simulations study of particle movements provide an alternative to conventional reservoir simulation by allowing the study of microscopic and/or macroscopic fluid flow, which is close to the scale of geological models. In this paper, the FHP-II (Frisch, Hasslacher and Pomeau - FHP) model of lattice gas automata were developed to study fluid flow in order to estimate the properties of heterogeneous porous media. Heterogeneity simulated by placing solid obstacles randomly in a two-dimensional test volume. Properties of the heterogeneous porous media were estimated by the shape, size, number of the obstacles and by the distribution of the obstacles within the volume. Results of the effects of grain sizes and shapes, and its distribution in the porous media on the tortuosity, effective porosity, permeability and displacement efficiency were obtained. An investigation of fluid flow and comparison with laboratory experiment were also presented. Reasonably good agreement between the lattice gas automata simulation and laboratory experiment results were achieved.